Silencing the Nucleocytoplasmic O-GlcNAc Transferase Reduces Proliferation, Adhesion, and Migration of Cancer and Fetal Human Colon Cell Lines - Steenackers, Agata; Olivier-Van Stichelen, Stéphanie; Baldini, Steffi F.; Dehennaut, Vanessa; Toillon, Robert-Alain; Le Bourhis, Xuefen; El Yazidi-Belkoura, Ikram; Lefebvre, Tony (Frontiers in Endocrinology, 2016)
The post-translational modification of proteins by O-linked β-N-acetylglucosamine (O-GlcNAc) is regulated by a unique couple of enzymes. O-GlcNAc transferase (OGT) transfers the GlcNAc residue from UDP-GlcNAc, the final product of the hexosamine biosynthetic pathway (HBP), whereas O-GlcNAcase (OGA) removes it. This study and others show that OGT and O-GlcNAcylation levels are increased in cancer cell lines. In that context we studied the effect of OGT silencing in the colon cancer cell lines HT29 and HCT116 and the primary colon cell line CCD841CoN. Herein we report that OGT silencing diminished proliferation, in vitro cell survival and adhesion of primary and cancer cell lines. SiOGT dramatically de-creased HT29 and CCD841CoN migration, CCD841CoN harboring high capabilities of mi-gration in Boyden chamber system when compared to HT29 and HCT116. The expression levels of actin and tubulin were unaffected by OGT knockdown but siOGT seemed to disor-ganize microfilament, microtubule and vinculin networks in CCD841CoN. While cancer cell lines harbor higher levels of OGT and O-GlcNAcylation to fulfill their proliferative and migra-tory properties, in agreement with their higher consumption of HBP main substrates glucose and glutamine, our data demonstrate that OGT expression is not only necessary for the biolog-ical properties of cancer cell lines but also for normal cells.